2016
DOI: 10.1007/978-3-319-22461-9_12
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Hotspots of Evolutionary History with Data from Multiple Phylogenies: An Analysis of Endemic Clades from New Caledonia

Abstract: The great bulk of the present knowledge of the Tree of Life comes from many phylogenies, each with relatively few tips, but with lots of diversity concerning taxa and characters sampled and methods of analysis used. For several biodiversity hotspots this is the kind of data available and ready to be used to have a better understanding on the evolutionary patterns and to identify areas with remarkable evolutionary history. But relying on data coming from independent studies raises some methodological challenges… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
3

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 44 publications
(31 reference statements)
0
5
0
Order By: Relevance
“…Although micro-endemicity has frequently been reported in researches for different groups of the New Caledonian fauna [ 10 , 14 , 16 , 23 , 26 27 , 31 ], the present study is the first to be specifically designed to quantify its distribution range, estimate its frequency, and determine the extent to which these findings are common to several taxonomic groups. It is also the first time that the distribution range of this fauna is analyzed taking sampling effort into account.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…Although micro-endemicity has frequently been reported in researches for different groups of the New Caledonian fauna [ 10 , 14 , 16 , 23 , 26 27 , 31 ], the present study is the first to be specifically designed to quantify its distribution range, estimate its frequency, and determine the extent to which these findings are common to several taxonomic groups. It is also the first time that the distribution range of this fauna is analyzed taking sampling effort into account.…”
Section: Discussionmentioning
confidence: 93%
“…Our results provide estimates of the distribution range in a wide range of species, which will facilitate the re-assessment of the status of species from at least 12 different orders ( S1 Table and S2 Table ). Considering the ongoing environmental pressure and destruction of several habitats in New Caledonia [ 10 , 19 23 ], the fact that all species with a distribution range <10 km 2 occur in a single locality, and that population sizes are frequently very small, and that very few of these species occur in areas legally protected, a great number of these micro-endemic species are very likely to be Critically Endangered.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…() showed that the distribution area of microendemic species increased considerably with time, placing the oldest endemics in secondary sympatry. In this context, some Quaternary forest climatic refuges could be centres of endemism for some groups at the least, but they do not necessarily equate to centres of diversity or even centres of origin where a significant amount of deep time evolution is conserved (Pellens et al., ). As an example, the most emblematical relict in New Caledonia, Amborella trichopoda , considered by many as the sister‐group of flowering plants, has a quite wide distribution on the island and is not restricted to particular areas of long‐term stability (Poncet et al., ; Pouteau et al., ).…”
Section: Forest Climatic Refuges = Centres Of Endemism = Centres Of Dmentioning
confidence: 99%
“…They are collected by direct search on their specific habitats, or, indirectly, by collectors searching for xylophagous insects. Adult males can be captured with light traps, although it rarely occurs [ 31 , 32 , 39 ].…”
Section: Methodsmentioning
confidence: 99%